Distribution of Endothelial Cell Protein C/Activated Protein C Receptor (EPCR) During Mouse Embryo Development - Crawley, James T. B.; Gu, Jian-Ming; Ferrell, Gary; Esmon, Charles T. (Thrombosis and Haemostasis, 2002)
The endothelial cell protein C receptor (EPCR) augments protein C activation by the thrombomodulin•thrombin complex. Deletion of the EPCR gene in mice has been reported to lead to embryonic lethality before embryonic day 10 (E10.0). To identify potential mechanisms responsible for this lethality, we performed an immunohistological analysis of EPCR distribution during mouse embryogenesis. EPCR was detected in the trophoblast giant cells at the feto-maternal boundary from E7.5 and at later time points in the trophoblasts of the placenta, suggesting a role in the haemostatic regulation of the maternal blood that irrigates these surfaces. In the embryo, EPCR was weakly detected in aortic endothelial cells from E13.5. Thereafter, EPCR levels increased in certain large blood vessel endothelial cells suggesting that the specificity of EPCR to large vessels is conferred in utero. However, not until postnatal day 7 did the intensity and distribution of EPCR staining mimic that observed in adult mice.Abbreviations: APC – activated protein C, AP – alkaline phosphatase, EC – endothelial cell, EPCR – endothelial cell protein C/activated protein C receptor, FITC – fluorescein isothiocyanate, HRP – horseradish peroxidase, PBS – phosphate-buffered saline, TM – thrombomodulin, WT – wild–type
Keywords: EPCR; development; coagulation; protein C; thrombomodulin